2018
DOI: 10.1073/pnas.1722147115
|View full text |Cite
|
Sign up to set email alerts
|

Single-stranded telomere-binding protein employs a dual rheostat for binding affinity and specificity that drives function

Abstract: SignificanceProteins that bind nucleic acids are frequently categorized as being either specific or nonspecific, with interfaces to match that activity. In this study, we have found that a telomere-binding protein exhibits a degree of specificity for ssDNA that is finely tuned for its function, which includes specificity for G-rich sequences with some tolerance for substitution. Mutations of the protein that dramatically impact its affinity for single-stranded telomeric DNA are lethal, as expected; however, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…In summary, the results of Glustrom et al (2018) nicely complement the conclusions inferred from previously published studies on the puzzling diversity of yeast telomeres as well as on the evolution of DNA-binding proteins. In more general terms, they also provide additional evidence that increasing perfection of molecular recognition does not necessarily mean an optimal evolutionary strategy (Kováč, 1987; Bar-Even et al, 2011).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…In summary, the results of Glustrom et al (2018) nicely complement the conclusions inferred from previously published studies on the puzzling diversity of yeast telomeres as well as on the evolution of DNA-binding proteins. In more general terms, they also provide additional evidence that increasing perfection of molecular recognition does not necessarily mean an optimal evolutionary strategy (Kováč, 1987; Bar-Even et al, 2011).…”
supporting
confidence: 84%
“…Recently, Glustrom et al performed an elegant systematic analysis of the effects of amino acid substitutions across the ssTBP of S. cerevisiae (Cdc13p) DNA-binding interface on its affinity and specificity toward heterogeneous telomeric repeats of the host cell (Glustrom et al, 2018). The authors showed that, as they expected, a subset of mutants exhibiting a significant loss in affinity in vitro also conferred a profound loss of viability in vivo .…”
mentioning
confidence: 99%
“…Furthermore, a mutation in CDC13 (cdc13-F539A) that reduced the ability of the t-RPA complex to associate with telomeres had a substantial effect on replication fork collapse. This mutation, located in a DNA contact residue on the surface of the high affinity DNAbinding domain of Cdc13 (19), reduced DNA binding in vitro as well as association of Cdc13 with telomeric chromatin (ref; SI Appendix, Fig. S10).…”
Section: A Collapsed Replication Fork Generates a Single Terminus Thamentioning
confidence: 99%
“…The effect was particularly pronounced when comparing sub-populations of the shortest telomeres, as the fraction of telomeres that retained ≤ 125 bp of founder DNA increased from 9.2% in wild type to 31.5% in the cdc13-F539A strain (p < 0.0001). Since the cdc13-F539A strain does not have a resection defect (19), this argues that the increased loss of founder sequence DNA was the consequence of an elevated frequency of fork collapse, rather than increased terminus-specific erosion.…”
Section: A Collapsed Replication Fork Generates a Single Terminus Thamentioning
confidence: 99%
See 1 more Smart Citation